2020
DOI: 10.3389/fnagi.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System and Cognitive Impairment in Older Patients: Evidence From Long-Term Heart Rate Variability in Real-Life Setting

Abstract: Background: In geriatric age, cognitive impairment and cardiovascular disorders are frequent comorbidities. Age-related anatomical and functional cardiac changes, including the autonomic system, could interfere with the control of different cognitive domains. Therefore, we assess the relationship between long-term heart rate variability (HRV), as a measure of autonomic nervous system (ANS) functioning, and cognitive performance in elderly patients representative of outpatients in a real-life setting. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…Observed to be associated with cognitive function (Dalise et al, 2020), HF and LF were selected for logistic regression analyses. In addition, as SDNNI, VLF, and ULF were associated with POD at a significance level of less than 0.2, they were also included in the planned binary logistic regression analyses.…”
Section: Postoperative Delirium and Heart Rate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Observed to be associated with cognitive function (Dalise et al, 2020), HF and LF were selected for logistic regression analyses. In addition, as SDNNI, VLF, and ULF were associated with POD at a significance level of less than 0.2, they were also included in the planned binary logistic regression analyses.…”
Section: Postoperative Delirium and Heart Rate Variabilitymentioning
confidence: 99%
“…Although studies have shown that HRV is associated with cognitive function in older patients (Kim et al, 2018;Dalise et al, 2020), there are few studies concerning the correlation between long-term HRV parameters and POD. As is proved in previous researches, HRV decreases to varying degrees in elderly patients after surgery, indicating that ANS activity and circadian rhythm were impaired after surgery (Marsch et al, 1994;Amar et al, 1998;Kärkelä et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent analyses of heart rate (HR) or heart rate variability (HRV) and blood-oxygen-level dependent (BOLD) signal at rest or during an emotional, cognitive, or motor task indicated that some additional cortical regions, such as dorsolateral PFC (dlPFC), exert influence on HRV in coordination with CAN, although they are not closely connected to the autonomic centers in the brain stem ( Napadow et al, 2008 ; Smith et al, 2014 ; Young et al, 2017 ). HRV corresponds to the variation in the time interval between two successive R waves and has been associated with the various cognitive ( Hansen et al, 2009 ; Dalise et al, 2020 ) and affective functions ( Melzig et al, 2009 ; Miller et al, 2019 ). Thayer and Lane (2000) put forward the neurovisceral integration (NVI) model centered on CAN regions and provided a framework for understanding the integration of cognitive, affective, and autonomic information.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to two scales focusing on the different aspects of function. The MMSE focuses on memory, while the MoCA focuses on executive function 19 . It is possible that different factors may contribute to various aspects of cognitive function decline 20 .…”
Section: Discussionmentioning
confidence: 99%